PENGARUH DUKUNGAN KELUARGA DALAM PEMBERIAN ASI EKSKLUSIF PADA IBU BEKERJA DI KOTA LANGSA - , Elmida AS, Prof. dr. Djauhar I., SpA(K)., MPH., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Estimated 4 million babies die each year due to infectious diseases, related to behaviors in which colostrums and exclusive breastfeeding are not practiced. Exclusive breastfeeding practice given to a baby for six months after birth in Indonesia (2006), in NAD Province (2008) and in Langsa Municipality was 32.3%, 10.39%, and 22.93%, respectively. Family support, workplace support, knowledge, and social economy affect a womanâs decision on breastfeeding her infant. Objective: To find out effects of family support on exclusive breastfeeding practice among working women in Langsa Municipality, Nanggroe Aceh Darussalam Province. Method: This was a quantitative study with a cross-sectional design located in Langsa Municipality. Population was working women in public institutions having a baby 6 months to < 11 years of age, living in Langsa Municipality. Sample taking used systematic random sampling with a sample size of 176 subjects. Data analysis used chi-square test and logistic regression. Result: The proportion of women who gave exclusive breastfeeding and who did not was 21.02% and 78.98%, respectively. The proportion of women who received family support and who did not was 30.11% and 69.89%, respectively. The proportion of women who received workplace support and who did not was 39.77% and 60.23%, respectively. The proportion of women who had higher and lower knowledge about breastfeeding was 36.36% and 63.64%, respectively. The proportion of women who had moderate and low social economic status was 82.38% and 17.61%, respectively. Bivariable analysis showed that there was a significant relationship between family support (PR=3.4: 95% CI=1.92-6.02), workplace support (PR=1.78: 95% CI=1.00-3.15), and knowledge (PR=2,29: 95% CI=1,29-4,07) and exclusive breastfeeding practice. However, there was no significant relationship between socio-economic status and exclusive breastfeeding practice (PR=0.66: 95% CI=0.34-1.26). In addition, multivariable analysis showed that the most dominant variables contributing to exclusive breastfeeding practice were family support (PR= 3.27